The Structuration of the Sexual Habitus of Youth Culture: An Exploratory Study of Some of the Sexual Dimensions of Youth Culture of the College of Social Sciences and Philosophy - Lanuza*, Gerry M. (Philippine Social Sciences Review; Vol 58 No 1: Jan 2006-Dec 2007, Ed. Jorge V. Tigno, 2009)
The College of Social Sciences and Philosophy (CSSP) is one of the biggest colleges in the University of the Philippines Diliman. It has a long illustrious history of being the citadel of political and intellectual ferment in the University. The distinctive character of the College can be traced to the nature of its academic program: the teaching of liberal arts. Bearing these almost mythical images in mind, there is a need to study the youth culture of the students of CSSP. Past studies have only addressed the social and political dimensions of its students. This study therefore investigates some of the sexual dimensions of CSSP youth culture. Findings show that CSSP students are not so different from the average Filipino youth. Filipino youth today still highly value close family ties; therefore, they are wary of social changes that might disrupt this traditional setting. The sexual habitus of CSSP students is shaped largely by their religious background. Because of modernizing currents and globalizing forces enveloping our country and the University, the trajectory of the sexual habitus of CSSP students will be a good ground for exploring young Filipinos’ response to modernization and postmodernization. __________ * Associate professor at the Department of Sociology, University of the Philippines Diliman. Email: glanuza@gmail.com.
Keywords: youth; culture; sexual habitus